2015
DOI: 10.1007/s13277-015-3299-0
|View full text |Cite
|
Sign up to set email alerts
|

Astemizole-based anticancer therapy for hepatocellular carcinoma (HCC), and Eag1 channels as potential early-stage markers of HCC

Abstract: Hepatocellular carcinoma (HCC) has very poor prognosis. Astemizole has gained great interest as a potential anticancer drug because it targets several proteins involved in cancer including the Eag1 (ether à-go-go-1) potassium channel that is overexpressed in human HCC. Eag1 channels are regulated by cancer etiological factors and have been proposed as early tumor markers. Here, we found that HepG2 and HuH-7 HCC cells displayed Eag1 messenger RNA (mRNA) and protein expression, determined by real-time RT-PCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…K Ca 3.1 could maintain the hyperpolarized membrane potential in cancer liver cells, which promotes Ca 2+ influx and facilitation of mitogenic activation [ 166 ]. Astemizole, a nonspecific inhibitor of K v 10.1 and K v 11.1 potassium channels, significantly decreased cell proliferation and increased apoptosis in vitro in the liver cancer cell lines HepG2 and HuH7 [ 167 ]. In the same study, the authors observed that astemizole clearly prevented HCC development in vivo .…”
Section: Cancermentioning
confidence: 99%
“…K Ca 3.1 could maintain the hyperpolarized membrane potential in cancer liver cells, which promotes Ca 2+ influx and facilitation of mitogenic activation [ 166 ]. Astemizole, a nonspecific inhibitor of K v 10.1 and K v 11.1 potassium channels, significantly decreased cell proliferation and increased apoptosis in vitro in the liver cancer cell lines HepG2 and HuH7 [ 167 ]. In the same study, the authors observed that astemizole clearly prevented HCC development in vivo .…”
Section: Cancermentioning
confidence: 99%
“…For example, astemizole has shown anti-cancer activity for cervical cancer, hepatocellular carcinoma, melanoma and breast cancer43444546. These reports suggested that the mechanism associated with the anti-cancer activities of astemizole were due to its on-target (H1 receptor) and off-targets (Erg potassium channels), as the histamine receptors and potassium channels have been found to play important roles in tumor cell homeostasis47484950.…”
Section: Discussionmentioning
confidence: 99%
“…Eag channels have also been detected in the normal retina [13,14]. In contrast, Eag1 is overexpressed in many cancer cell lines and human tumors, including those from the liver, cervix, lung, breast, and colon [11,13,[15][16][17][18][19]. Interestingly, the human Eag-related channel (Herg1), which is very relevant for cardiac repolarization [20], has been found to be overexpressed in retinoblastoma samples from patients that did not benefit from conservative treatment, namely chemotherapy followed by cryotherapy and/or laser treatment [21].…”
Section: Introductionmentioning
confidence: 99%